Promosi Kesehatan Pencegahan Covid-19 di Kampung Batu Gede Desa Cilebut Barat Tahun 2021: Covid-19 Prevention Health Promotion in Batu Gede Village, West Cilebut Village in 2021 - Qisti, Dewi Anissa; Putri, Elwan Nanda Eka; Sulaeman, Erlangga; Fitriana, Hafifah (Journal of Public Health Education, 2022)
Introduction: At the end of 2019, to be precise in December, the world was shocked by an incident that made many people anxious, caused by the coronavirus. This incident began in Wuhan, China, Hubei Province, and has spread rapidly throughout China. This epidemic spread so quickly throughout the world. Objective: This research aims to determine the knowledge and changes in attitudes of the people of Batu Gede, West Cilebut Village toward preventing COVID-19. Methods: This research takes the form of formulating a health survey problem, the media used in this research uses Google Forms or qualitative descriptive media via Questionnaires. Respondents numbered 50 people. Results: Based on research results from 50 respondents from the people of Batu Gede Village, West Cilebut Region, 50% have not fully implemented COVID-19 prevention and there is still a lack of awareness among the people of Batu Gede Village, West Cilebut Region regarding the spread and prevention of Covid-19. Conclusion: Based on the results of a health survey on COVID-19 prevention behavior in Batu Gede Village, West Cilebut Region in 2021, there are still many people who have not adopted a healthy lifestyle, such as regularly changing masks, consuming vitamin C, and sunbathing in the morning. Based on the group analysis, there is 1 priority problem point, namely that there are still many people who have not been vaccinated, and the activities of providing free vaccinations are not yet comprehensive.